Study to Assess the Effectiveness of Structured Teaching Programme on Hospice and Palliative Care among Nursing Students - Kanika Guleria; Mandeep Kaur; Amandeep Kaur (Institute of Medico-legal Publications Pvt Ltd, 2021)
Context: Patient and family who are confronting the issues of life threatening diseases achieves personalgratification through palliative care.Aim: The primary goal of the investigation was to determine the adequacy of “structured teachingprogramme” on hospice and palliative care amidst nursing students.Setting: Quasi experimental study was conducted in Kular College of Nursing, Kishangarh.Methods and material: “Non-probability-convenience sampling technique was utilized to select sample.60 subjects were selected for the study. Self structured knowledge questionnaire was used for data collection.Results: The outcomes indicated that pre test mean score” was 16.86 & standard deviation was 3.1 while“post-test mean score” was 23.46 & standard deviation was 4.14.Conclusion: “Structured Teaching programme” was efficacious in enhancing knowledge of nursing students.